Proposals for the development of the Cape of Good Hope Nature Reserve : annexure to thesis - Binckes, Graeme (School of Architecture, Planning and Geomatics, 2020)
The Cape of Good Hope Nature Reserve occupies the southern end of the Cape Peninsula and thus of the Southern Peninsula Subregion referred to in the general study (photographs 2 and 29). The Reserve has an area of nearly 29 1/2 square miles; its coastline is some 24 miles in length. It is used both as a Nature Reserve and as a recreation area, the latter function being concentrated, in the main, within restricted coastal sites; apart from these, Cape Point is a considerable tourist attraction as is the drive through the Reserve. Existing access routes and travelling times to the Reserve are shown on Map No. 5.1, together with current proposals.